The Textual Presence of Women between Poetics and Systematics A Critical Approach to Selected Models from Abbasid Poetic Discourse: A Critical Approach to Selected Models from Abbasid Poetic Discourse (Journal of Hama University, 2025)
This research addresses the textual presence of women in Abbasid poetic discourse through its poetic and systematic dimensions. It aims to provide a critical artistic and cultural examination of selected models from Abbasid poetic discourse, framing a systematic textual presence of the signifier “woman” with its partial themes and semantic circles that unfold in the lexeme field of “woman.” This approach combines aesthetic and cultural visions and employs deep deconstructive tools towards the essential textual structures and dynamic systematic elements that guide meaning, without neglecting the aesthetic level of structural formations and their poetic paths.    The poetics of the signifier “woman” flow in the paths of semantic circles of symbol and heritage. The former culminates in crystallizing the symbolic dimension of women, while the latter presents the signifier “woman” as a central partial theme of the traditional structural framework of Arabic poetry. Between Sufi symbolism and inherited artistic methodology, which retransmits the motifs of artistic heritage, the poetics of the textual presence of women flow into diverse structural formations. These formations depict scenes of love and parting at the poetic level of language, accompanied by their symbolic and rhetorical counterparts. Conversely, the systematic nature of the signifier “woman” flows in the path of material and moral dispossession, and the path of cultural modeling. In their semantic circles, systematic meaning takes shape and crystallizes deeply at the implicit level, while its cultural markers in the surface structure consistently allude to their referential connotations.
Keywords: Textual presence; systematics; poetics; Abbasid poetic discourse